Nested PCR in magnetically actuated circular closed-loop PCR microchip system - Lok, Khoi Seng (2012)
We demonstrate a new and sensitive amplification technique (referred to as Nested Polymerase Chain Reaction; nPCR). It based on a magnetically actuated circular closed-loop PCR microchip system. nPCR involves the use of two sets of primers in two successive PCR runs, and allows the amplification of a single locus from a minute quantity of template DNA. Two sets of primers are specially designed to a target 500-bp region of the bacteriophage lambda template DNA in the first PCR run, and a 247-bp region of the targeted 500-bp first PCR product in the second PCR run. PCR is run on the microchip system and concurrently in regular thermocycler for comparison. The products are analyzed by conventional agarose gel electrophoresis. The detection limit for the initial template DNA is 1.63 × 105 copies per μL (or 8.67 pg) for the first PCR run, and 1.63 copies per μL (or 0.0867 fg) for the second run. The results are comparable to a regular thermocycler. This preliminary study opens a new gateway to future development of specialized nPCR on chip.